Research on the pathogen causing root rot on Phyllanthus emblica from the perspectives of identification, bionomics, fungicide sensitivity assay, and transcriptome analysis under different pH stress - Zhang, Yiming; Song, Minyan; He, Yonghong; Si, Yehua (Frontiers in Microbiology, 2025)
In recent years, Phyllanthus emblica root rot disease has occurred in Yunnan and caused significant economic losses to local plantation farmers, the pathogen was identified as Diaporthe eres through morphological and molecular method. The indoor toxicity testing and biological characteristic research on Diaporthe eres were carried out. Additionally, the transcriptional regulatory mechanism under different pH stress conditions was studied. The results showed that Prochloraz had the strongest inhibitory effect on Diaporthe eres mycelial growth, with an EC50 value of 0.059 mg·L-1. Diaporthe eres grows best in an environment of 26°C, 12: 12 alternating light, and pH 6. Go enrichment analysis revealed that the differentially expressed genes were mainly related to the biosynthesis of ribonucleoprotein complexes, ncRNA metabolic processes, ribosome and so on. KEGG analysis shows that in acidic environments, Diaporthe eres responds to external stress by precisely regulating amino acid metabolism and ribosome function, while in alkaline environments, it helps cells respond to and perceive external stress by forming multi-level adaptive networks and inhibiting activities such as protein synthesis transcription. This study provides relevant references for the prevention and control of this disease.